Systematics of the Nososticta salomonis complex (Odonata: Zygoptera: Platycnemididae) - Theischinger, Günther; Mitchell, Andrew; Richards, Stephen J.; Polhemus, Dan A. (Zootaxa, 2023)
We examined the morphology, colour patterns and genetic relationships of Nososticta populations allied to N. salomonis (Selys) from across Melanesia. Seven species-level taxa are recognised in the N. salomonis ‘complex’: N. africana (Schmidt), N. boonei sp. nov., N. chrismulleri Theischinger & Richards, N. hedigeri sp. nov., N. salomonis (Selys), N. stueberi sp. nov., and N. tagula sp. nov. All of these species are black damselflies with blue markings, and they differ from all other Nososticta by having: 1) a prominent spike on the male superior appendage, 2) a prominent angular base of the male inferior appendage, and 3) a complex posterior lobe on the female pronotum bearing two pairs of processes in the rough shape of a chair when viewed laterally. A molecular phylogeny based on the DNA barcode fragment of the COI gene plus two nuclear genes indicates that these seven species are closely related, but more extensive sampling of Nososticta species is required to confirm that they form a monophyletic group.